2020
DOI: 10.1021/acs.chemmater.0c02806
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Analysis and Formability of the Cubic A2BX6 Vacancy-Ordered Double Perovskite Structure

Abstract: A geometric analysis of the cubic A2BX6 structure commonly formed by metal halides is presented. Using the 'hard sphere' approximation, where the ions are represented by spheres of a fixed radius, we derive four limiting models that each constrain the distances between constituent ions in different ways. We compare the lattice parameters predicted by these four models with experimental data from the Inorganic Crystal Structure Database (ICSD). For the fluorides, the maintenance of the AX bond length at the sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 57 publications
(103 reference statements)
0
28
0
Order By: Relevance
“…To date, reports describing the degradation mechanism of Sn perovskites remain limited, in contrast with Pb-based analogues 47 53 . For example, some studies have shown that ASnX 3 (A = Cs + , MA + or FA + ; X = I - , Br - ) can decompose in air to form A 2 SnX 6 (vacancy-ordered double perovskite 54 ) and SnO 2 31 , 55 57 , while others revealed that FASnI 3 and (PEA) 2 SnI 4 (where PEA refers to phenylethylammonium) degrade in the presence of oxygen to SnI 4 , SnO 2 and FAI/PEAI 58 , 59 . Whilst these findings provide plausible air-mediated decomposition routes of Sn-based perovskites, a more detailed understanding of the degradation mechanism as well as knowledge of inconspicuous reaction pathways is required.…”
Section: Introductionmentioning
confidence: 99%
“…To date, reports describing the degradation mechanism of Sn perovskites remain limited, in contrast with Pb-based analogues 47 53 . For example, some studies have shown that ASnX 3 (A = Cs + , MA + or FA + ; X = I - , Br - ) can decompose in air to form A 2 SnX 6 (vacancy-ordered double perovskite 54 ) and SnO 2 31 , 55 57 , while others revealed that FASnI 3 and (PEA) 2 SnI 4 (where PEA refers to phenylethylammonium) degrade in the presence of oxygen to SnI 4 , SnO 2 and FAI/PEAI 58 , 59 . Whilst these findings provide plausible air-mediated decomposition routes of Sn-based perovskites, a more detailed understanding of the degradation mechanism as well as knowledge of inconspicuous reaction pathways is required.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite QDs may be organic-inorganic hybrids or fully inorganic; and are represented by the chemical formula ABX 3 (e.g., CsPbI 3 or CsPbBr 3 ) 50,51 in which A is an inorganic monovalent cation (such as caesium, Cs + ) or an organic cation (such as methylammonium, CH 3 NH 3 + , or formamidinium, (NH 2 ) 2 CH + ), 52 B is an inorganic-metal cation such as lead (Pb) or tin (Sn); and X is an anion, such as oxygen, halogens, or alkali metals. 49,[53][54][55][56] 1.2.2 Structure. Structurally, metallic QDs occur in three basic forms: the core, core/shell or alloyed types (Fig.…”
Section: Physicochemical Properties Of Qdsmentioning
confidence: 99%
“…16 Theo. 17 F I G U R E 1 Volume optimization plot for Rb/Cs 2 TeI 6 n(λ) in wavelength range of 250-750 nm as visible range is 400-700 nm. Figure 3A elaborates the dispersion behavior of Rb/Cs 2 TeI 6 in term of Ɛ 1 (λ).…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Brik and Kityk 16 calculated lattice constant for Cs 2 TeI 6 from their developed analytical technique. Rahim et al 17 also calculated the lattice constant for Cs 2 TeI 6 at analytical level. Up till now, the optical and thermoelectric properties neither reported experimentally nor theoretically while electronic properties were not studied theoretically.…”
Section: Introductionmentioning
confidence: 99%